Three foundations A competitive, sustainable, inclusive Europe - Bending, Tim (European Investment Bank, 2019)
Europe faces a historic opportunity. We need to reimagine European unity as a collective endeavour, as the only way in which we can turn threats to our way of life into the possibility to create a better life for all. This report focuses on three core areas where EU-wide political ambition and investment are truly necessary: Rapid technological change amid increasing global competition, with digital technologies set to have dramatic impacts across all sectors of the economy. Europe needs to become more competitive through innovation and the fast absorption of new technologies if it is to reap the benefits of this wave of change. Increasing breakdown of the global climate and other ecosystems due to our economic system, with action on mitigation - and to adapt to already inevitable changes - now incredibly urgent. In part, this is because of the time lags built into natural systems. In part, it is because of the unavoidable path-dependency and pace of our own response. Growing threats to social cohesion and social sustainability from multiple trends, including how we manage technological change and automation, the climate transition, and societal ageing. This is happening against a background of stalling convergence across Europe, rising income inequality over several decades, rising burdens on households and persistent inequalities of opportunity that are also a drag on economic performance. Competitiveness, sustainability and inclusion have to be addressed together, holistically. This is why this report addresses all three with a focus on the complex interlinkages between them. The vital role of far-sighted investment is a key theme that emerges from this investigation. The critical role of European-level collaboration is another. Instead of merely adapting to change, we need to be proactive through timely reform and investment that sets us on a pathway towards a society that is productive, sustainable and inclusive, by design.